2017
DOI: 10.1007/s00441-017-2573-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary innate inflammatory responses to agricultural occupational contaminants

Abstract: Agricultural workers are exposed to many contaminants and suffer from respiratory and other symptoms. Dusts, gases, microbial products and pesticide residues from farms have been linked to effects on the health of agricultural workers. Growing sets of data from in vitro and in vivo models demonstrate the role of the innate immune system, especially Toll-like receptor 4 (TLR4) and TLR9, in lung inflammation induced following exposure to contaminants in agricultural environments. Interestingly, inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 148 publications
0
28
0
Order By: Relevance
“…The occupational hazards of farming are the subject of the review by Sethi et al (2017). They provide an overview on the contaminants that agricultural workers are exposed to and their effects on the innate immune system and the inflammatory state of the lung, with particular emphasis on Toll-like receptors and surfactant proteins.…”
Section: Remodelingmentioning
confidence: 99%
“…The occupational hazards of farming are the subject of the review by Sethi et al (2017). They provide an overview on the contaminants that agricultural workers are exposed to and their effects on the innate immune system and the inflammatory state of the lung, with particular emphasis on Toll-like receptors and surfactant proteins.…”
Section: Remodelingmentioning
confidence: 99%
“…The studies regarding interaction of LPS and pesticide on cytokine expression [13]; apoptosis [14] and lung immunity [15] suggested synergistic effect of the combination of LPS with pesticide compared to pesticide alone. We have reported that LPS interacts with various classes of pesticides to alter the magnitude of pulmonary damage [2,[16][17][18][19][20][21] as well as genotoxicity [7,22]. Thus, exposure to LPS may deteriorate the health of ethion exposed subjects by exaggerating the harmful effects of ethion.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural workers especially those in animal confinement or grain handling buildings may potentially get exposed to both pesticides and environmental bacterial lipopolysaccharides (LPS) [5]. Previous studies from our laboratory indicate that endotoxin interaction with various classes of pesticides increases the pesticide induced lung damage [6][7][8][9][10]. LPS ligate TLR-4 to activate various signaling pathways including NF-kB leading to the production of inflammatory mediators and lung inflammation [11].…”
Section: Introductionmentioning
confidence: 99%